Vestibulovaginal Sclerosis Versus Lichen Sclerosus. (July 2018) - Day, Tania; Burston, Kate; Dennerstein, Graeme; Pagano, Ross; Scurry, James
Abstract : To determine if vestibulovaginal sclerosis and lichen sclerosus (LS) are 2 distinct entities. Biopsies obtained from the vagina or vulvar vestibule that contained abnormal subepithelial collagen were reviewed. Cases were categorized either as LS or vestibulovaginal sclerosis based on presence or absence of basal layer degeneration and lymphocytic infiltrate. Clinical data collected included examination findings, biopsy site and indication, previous vulvovaginal surgery, medications at time of biopsy, vulvar LS, treatment, and response. There were 15 cases with a mean age of 62 yr (range: 32–86 yr); 12 (80%) specimens were from vestibule and 3 from vagina. Nine cases were categorized as LS because of lymphocytic infiltrate in combination with basal layer degeneration, of these 8 had LS elsewhere on vulvar skin. Six cases were classified as vestibulovaginal sclerosis and had an absent or sparse lymphocytic infiltrate and essentially normal epithelium; none of these had vulvar LS. While vestibulovaginal sclerosis and lichen sclerosus are distinguishable clinically and histopathologically, further studies are needed to determine if vestibulovaginal sclerosis is a subset of LS or a different condition.